Agroecology and local development in coffee communities of the Colombian Coffee Cultural Landscape - Rueda-Rodríguez, Héctor Fernando; Perafán-Cabrera, Aceneth; Carvajal-Escobar, Yesid (Revista de Ciencias Agrícolas, 2024)
This article delves into the sociocultural determinants driving local development, focusing on coffee-growing communities in southwestern Colombia. Through interviews, focus groups, and participant observation, a detailed analysis is conducted in a region globally recognized for its cultural and environmental significance. The findings highlight the benefits of traditional agroecological systems, which contribute to environmental conservation, economic development, and community strengthening. Based on our findings, we can conclude that agroecology and cultural identity are key elements for the sustainability of the coffee cultural landscape, reinforcing the relevance of collaboration among local actors and the design of public policies focused on these practices.